2020
DOI: 10.1017/s027226312000039x
|View full text |Cite
|
Sign up to set email alerts
|

Even in the Best-Case Scenario L2 Learners Have Persistent Difficulty Perceiving and Utilizing Tones in Mandarin

Abstract: Lexical tones are widely believed to be a formidable learning challenge for adult speakers of nontonal languages. While difficulties—as well as rapid improvements—are well documented for beginning second language (L2) learners, research with more advanced learners is needed to understand how tone perception difficulties impact word recognition once learners have a substantial vocabulary. The present study narrows in on difficulties suggested in previous work, which found a dissociation in advanced L2 learners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 65 publications
(94 reference statements)
2
21
2
Order By: Relevance
“…Taken together, the excellent tone identification paired with chance performance for tone nonwords suggested to us that auditory tone perception is unlikely to be the primary source of L2 tone word recognition difficulty. A follow-up study used more clearly produced (non)words and once again found a strong difference between tone and vowel nonwords (Pelzl et al, 2020).…”
Section: Three General Explanations For L2 Tone Word Processing Difficultiesmentioning
confidence: 94%
See 4 more Smart Citations
“…Taken together, the excellent tone identification paired with chance performance for tone nonwords suggested to us that auditory tone perception is unlikely to be the primary source of L2 tone word recognition difficulty. A follow-up study used more clearly produced (non)words and once again found a strong difference between tone and vowel nonwords (Pelzl et al, 2020).…”
Section: Three General Explanations For L2 Tone Word Processing Difficultiesmentioning
confidence: 94%
“…Finally, an L2 listener may have difficulty with phonolexical representations, that is, encoding the lexical units of speech in their mental lexicon. This difficulty may lead to a variety of issues for tone representations: they may be entirely missing, incorrect, only known with some degree of uncertainty, or even confidently incorrect (Pelzl et al, 2020). If a given representation is not faithful to the actual form of the spoken tone word, this has the potential to lead to a variety of problems during lexical access.…”
Section: Three General Explanations For L2 Tone Word Processing Difficultiesmentioning
confidence: 99%
See 3 more Smart Citations